How to Implement Discovery Learning in English Language Teaching at Indonesia Higher Education? - Rafiqa Rafiqa; Marhaeni Sabil; Muhammad Aswad (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to investigate the implementation of discovery learning in teaching English. This study was qualitative research, and it applied a case study. The researcher conducted her study at Universitas Sulawesi Barat Majene Regency West Sulawesi. The data source was from the sample research, and purposive sampling was the selected technique in this study. The researcher is a primary instrument in this case study research. The findings release there were six steps of discovery learning implementation. The lecturers carried out the process of discovery learning, which consists of six steps. The frequency of implementation of discovery learning can be described into different categories, namely: High Implemented Discovery Learning (HIDL), Moderate Implemented Discovery Learning (MIDL), and Law Implemented Discovery Learning (LIDL). All lecturers are the High Implemented Discovery Learning is marked by the highest frequency of using discovery learning in teaching English education students. The stages of this implementation are stimulation, problem identification, data collection, data processing, verification, and generalization. The highest frequency of using marked the selection of each category discovery learning in teaching English.